A Fossil Paleozoic Subduction-Dominated Trench-Arc-Basin System Revealed by Airborne Magnetic-Gravity Imaging in West Junggar, NW China - Zheng, Qifang; Xu, Xi; Zhang, Wan; Zheng, Yuzhou; Liu, Yinghui; Kuang, Xingtao; Zhou, Daoqing; Yu, Xuezhong; Wang, Baodi (Frontiers in Earth Science, 2021)
A Carboniferous trench-arc-basin system related to oceanic-slab subduction has been well imaged by various geophysical probing and proposed for the formation of West Junngar, Northwest China, located in the southwest of the Central Asian Orogenic Belt. However, the origin of West Junggar remains contentious. Here we present an integrated aeronautic magnetic-gravity observation to further identify the trench-arc-basin system and constrain the subduction mode. By deploying an integrated aerial magnetic-gravity survey consisting of 66,000 survey-line kilometers from August 3 2015 to April 22 2016, we determine the magnetic and gravity anomaly across the study region using geophysical potential-field processing. Our results reveal curial crust-scale variations in magnetic and gravity structure beneath the West Junggar. It is notably demonstrated that the Tacheng basin is expressed by high-frequency back-arc rifting-related magnetic signal, and that a pronounced Bouguer-gravity high is located between the Durbut and Karamay-Urho faults, likely corresponding to a trapped oceanic lithosphere. Constrained by these comprehensive geological and geophysical observations across the West Junggar, we further upgrade and revise the previous model of West Junggar trench-arc-basin system related to a fossil intraoceanic subduction during the Late Paleozoic.